Inhomogeneous Diophantine approximation over fields of formal power series - Bugeaud, Yann; Singhal, L.; Zhang, Zhenliang (MATHEMATICA SCANDINAVICA, 2020)
We prove a sharp analogue of Minkowski’s inhomogeneous approximation theorem over fields of power series F_q((T^-1)). Furthermore, we study the approximation to a given point y in F_q((T^-1))^2 by the SL_2(F_q[T])-orbit of a given point x in F_q((T^-1))^2.